Pengaruh Kualitas Pelayanan Terhadap Keputusan Pelanggan Ramses Studio Di Bandar Lampung - Taufik Ramadani; Aripin Ahmad (BULLET : Jurnal Multidisiplin Ilmu, 2023)
The quality of customer service has an impact on customer decisions, and customer decisions will affect customer loyalty. One of the businesses that has enlivened the competition in the field of photography with the concept of young people in Bandar Lampung is Ramses Studio which is also engaged in photography services. Studio Management must always pay attention to aspects that can influence consumer behavior to use photo services, namely in the form of several limitations on the composition of service services, namely tangible, reliability, responsiveness, assurance, and empathy. The problem is whether service quality influences consumer purchasing decisions for visitors to Ramses Studio Photography Bandar Lampung services. The purpose of this study was to determine whether service quality influences consumer purchasing decisions for visitors to Ramses Studio Photography Bandar Lampung services. Based on the results of the discussion with multiple regression statistically, consumer purchasing decisions for visitors to Ramses Studio Photography Bandar Lampung services are jointly influenced by the independent variables Tangibles (X1), Reliability (X2), Responsiveness (X3), Assurance (X4) and Empathy (X5). Overall, the independent variables influencing customer decisions can be shown by the value of the coefficient of determination R2 = 0.404 or 40.40%, all independent variables affect customer decisions and the remaining 59.60% are influenced by other factors not identified or examined in this research.